Staging by imaging in gynecologic cancer and the role of ultrasound: an update of European joint consensus statements - Fischerova, Daniela; Smet, Carolina; Scovazzi, Umberto; Sousa, Diana Natacha; Hundarova, Kristina; Haldorsen, Ingfrid Salvesen (International journal of gynecological cancer, 2024)
In recent years the role of diagnostic imaging by pelvic ultrasound in the diagnosis and staging of gynecological cancers has been growing exponentially. Evidence from recent prospective multicenter studies has demonstrated high accuracy for pre-operative locoregional ultrasound staging in gynecological cancers. Therefore, in many leading gynecologic oncology units, ultrasound is implemented next to pelvic MRI as the first-line imaging modality for gynecological cancer. The work herein is a consensus statement on the role of pre-operative imaging by ultrasound and other imaging modalities in gynecological cancer, following European Society guidelines.
Keywords: Ultrasonography; cross-sectional studies; vulvar and vaginal cancer; cervical cancer; Genital Neoplasms, Female; pánev; Gynecology; nádory ženských pohlavních orgánů; lidé; ženské pohlaví; Humans; konsensus; Pelvis; Consensus; gynekologie; ovarian cancer; Female; uterine cancer; ultrasonografie